Sistem Pembantu Keputusan Penerima Karyawan Menggunakan Metode TOPSIS di PT Trans Media Corpora - Ade Onny Siagian; Hadion Wijoyo (Mahesa Research Institute, 2021)
Visionet Data Internasional Inc is one of the largest companies in the field of IT management service providers in Indonesia. For this achievement, the company needs employees with quality in accordance with the criteria needed. But in reality, there are still many companies that experience difficulties in the process of hiring employees. This is cause by many factors such as the many assessment criteria that serve as benchmarks in the recruitment process.One way to solve this problem is to create a decision support system that applies one of the MCDM methods. TOPSIS is a MCDM method that can be used in the decision support system. This method provides the advantages of concepts that are simple and easy to understand, computationally efficient and can measure the relative performance of alternative decisions in a simple mathematical result. In this research, a decision support system is designed that can be used by companies to provide alternative decisions in the employee recruitment process. The result of this research is a decision support system that can be used by the HRD Admin to assist the employee recruitment process.